Youth Satisfaction and Trust in The Sustainability of BUMDes during The Covid-19 Pandemic - Wicaksono, Alifinda Candy; Pertiwi, Vi’in Ayu; Handono, Setiyo Yuli (Politeknik Pertanian Negeri Payakumbuh, 2022)
The covid-19 pandemic had made the tourism sector managed by BUMDes Raharjo experience a decrease in the number of tourists. In 2020 also BUMDes Raharjo suffered losses in the form of debts to strawberry farmers so that employees were temporarily not given any salaries. The number of youth working in BUMDes decreased from 15 people in 2019 to 8 people in 2020. In 2021, only 5 young men remained in BUMDes Raharjo. This is due to the lack of youth trust in BUMDes. In addition, youth satisfaction also affects the confidence of youth. Satisfaction is related to the spirit and loyalty that youth give to BUMDes. This study aims to analyze the effect of satisfaction on the confidence of pandan village youth to BUMDes Raharjo. The research was conducted at BUMDes Raharjo located in Pandan Hamlet, Pandanrejo Village, Bumiaji Subdistrict, Batu City in May-June 2021. Research conducted using a quantitative approach. The population studied in this study was the youth of Pandan Hamlet aged 16 to 30 years. The sampling method used is accidental sampling. The data analysis methods used in this study are simple linear regression and partial test (T-test) through SPSS applications. The dependent variable is youth trust. The independent variable is youth satisfaction. The results showed satisfaction had a positive and significant effect on confidence in the T-test.